The Conflict Between Freedom of Speech and Freedom from Discrimination in Social Media Platforms : How “Free Speech Absolutism” Threatens Freedom from Discrimination on Twitter? - Kulmala, Maria (My University, 2023)
This thesis researches the problematic relationship between freedom of expression and freedom from discrimination in social media platforms. The thesis approach is socio-legal mixed with empirical methods. The motivation of the thesis is the recent buyout of Twitter by Elon Musk and the ‘free speech absolutism’ -policy that Musk and his fans support. This thesis demonstrates how such policy can harm society, especially underprivileged people, and analyses the possible consequences if such policy is widely accepted. The intention might be good when people can practice their right to freedom of expression to its full potential, but the reality is more complicated. In the last chapter, this thesis gives recommendations on how restrictions to freedom of expression online could be regulated effectively with shared responsibility between government and private companies. It is not an ideal situation that only private companies with financial perspective are the ones who decide which kind of content is allowed and which is prohibited.
Keywords: human rights, freedom of expression, freedom from discrimination, restrictions to human rights, social media